The regulation of religious dress of teachers in state schools: unnecessary intrusion or healthy separation of religion and the state? - Tie, F.H.; Russo, C.J. (2010)
After essentially remaining a non-issue for many years, serious questions and litigation have begun to emerge over whether teachers in state funded schools in such Nations as Australia, Malaysia, New Zealand, and the United States can wear distinctly religious dress to school. Not unexpectedly, these controversies have reached mixed results educators in some countries have allowed teachers to wear religious clothing to schools while others have placed a complete ban on such dress. In light of the nascent legal controversies on point, this presentation, which examines the status of religious garb in public schools as one more aspect of educators’ lives that is subject to increasing state regulation, is divided into three substantive sections. In order to set the context, the first section reviews briefly relevant international documents on religious freedom as a fundamental right. The second section reviews the constitutional provisions and legal controversies that have arisen primarily in Malaysia and the United States while also examining controversies that have surfaced Australia and New Zealand. Aware of the need to address the situation wherever it occurs, the final part paper offers policy recommendations for educators who face the controversial topic of whether educators should be permitted to wear distinctly religious garb in public schools. The paper rounds out with a brief conclusion.